Extracellular invertase is involved in the regulation of clubroot disease in Arabidopsis thaliana - Siemens, Johannes; Wolf, Sebastian; Greiner, Steffen; Rausch, Thomas (Molecular plant pathology, 2010)
Clubroot disease of Brassicaceae is caused by an obligate biotrophic protist, Plasmodiophora brassicae. During root gall development, a strong sink for assimilates is developed. Among other genes involved in sucrose and starch synthesis and degradation, the increased expression of invertases has been observed in a microarray experiment, and invertase and invertase inhibitor expression was confirmed using promoter::GUS lines of Arabidopsis thaliana. A functional approach demonstrates that invertases are important for gall development. Different transgenic lines expressing an invertase inhibitor under the control of two root-specific promoters, Pyk10 and CrypticT80, which results in the reduction of invertase activity, showed clearly reduced clubroot symptoms in root tissue with highest promoter expression, whereas hypocotyl galls developed normally. These results present the first evidence that invertases are important factors during gall development, most probably in supplying sugars to the pathogen. In addition, root-specific repression of invertase activity could be used as a tool to reduce clubroot symptoms.